Clinical Characteristics of 5 Phenotypes of Coenzyme Q10 Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Columbia University Medical Center, New York; University of Genoa, Italy; and University of Granada, Spain reviewed 149 cases of coenzyme Q10 (ubiquinone) deficiency, including their own cohort of 76 patients diagnosed from 1997-2010.